PECULIARITIES OF PATHOGENESIS OF THE GARDEN STRAWBERRY WHITE SPOTS IN CONDITIONS OF THE EASTERN PART OF UKRAINE’S - Turenko В.; Syniavin А. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
The article presents findings of the studies devoted to the bioecological features of development of the Ramularia tulasnei Sacc. strawberry white spots. The maximum manifestation of the disease was observed in July. The area of necrotic spots on the leaf blades of plants ranged from 5.7 to 27.8 % depending on the degree of damage. It caused general weakening of the bushes, reduction of yields, and deterioration of the berry quality in the current and subsequent years because of dying 25–28 % of the assimilating surface of strawberries leaves and a decrease in yield by 22–25 %. The disease spots from 0.7 to 8.2 mm in diameter appeared on the plants in late April and early May, and 7–10 days later a white or slightly brown plaque of conidial sporulation was observed. The incubation period lasted from 8 to 14 days. The optimum temperatures for the disease development were +20 – - +24 °С and the average daily air humidity was 75–80 %. During the vegetation period the pathogen was spread by conidia. The knowledge of the bioecological features of the disease development enables planning and carrying out effective protective measures to limit the spreading and development of strawberry white spots. To protect highly susceptible strawberry varieties, it is necessary to apply breeding-genetic, agro-technical measures and to use biofungicides: phytosporin with a consumption rate of 1 kg/ha and phytodoctor - 2 kg/ha. For industrial and private farms in the eastern part of the forest-steppe of Ukraine, it is advisable to use Roxana and Prisvyat varieties with increased resistance to garden strawberry spotting and the latest fungicides: Topaz 10% k.e. (0.3 l/ha); Chorus 75% v.g. (0.7 kg/ha). The first spraying in the phase of growth of young leaves, the second in the phase of extension of flower stalks.